The obesity paradox - Is BMI associated with advanced stage in oral cancer? - Junaid Anwar, Faraz Baig, Fouzia Shaikh, Najia Tabassum, Santosh Kumar, Syeda Zehra Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Recent studies have shown that cancer patients with low BMI have poor outcomes. Their results suggest, obesity have some protective effect in cancer termed as “obesity paradox”. Aim: To examine the association of BMI with prognostic indicators of oral squamous cell carcinoma (OSCC). Methodology: This multicenter cross-sectional study was conducted during the year 2020 and 2021. 126 patients recently diagnosed with OSCC were randomly selected from three different tertiary care setup in Karachi. Height and weight of each subject was recorded to calculate BMI and clinicopathological data was obtained. The BMI indices were categorized into low, normal and high strata according to WHO guidelines. Statistical analysis was done for association of independent factors with BMI strata. Results: We found 81(64.3%) participants were underweight compared to 32(25.4%) normal-weight and 13(10.3%) overweight cases. A strong statistical association was observed between low BMI (83.1% underweight) and advanced tumor stage i.e., Stage IV (P= 0.001) while among risk factors of OSCC, only smokeless tobacco showed significant association (P= 0.002) with reduced BMI. This research brings attention to the importance of BMI in cancer and add to the growing literature in the field of oncology. Our findings about the impact of BMI on OSCC outcome will help in the intervention and development of prevention strategies for one of the most prevalent cancers in Pakistan. This present research will help to answer the complex question of “optimum” BMI in cancer and will help to improve the prognosis of OSCC. Conclusion: Our findings suggested that low BMI could be an indicator of poor clinical outcomes in OSCC. We thus recommend monitoring of BMI in OSCC patients in order to optimize treatment strategies. However, we encourage further studies to examine other body composition metrics for individualized treatments and intervention strategies. Keywords: Adiposity, Obesity paradox, Squamous cells, carcinoma, BMI